Assessment of Glycaemic Effect of Benincasa hispida Aqueous Extract in Streptozotocin Diabetic Rats - Zakaria, Fatariah; Wan Rosli, W. I.; Ng, Sze Han; Zain , Mohd Shazwan; Wan Ahmad, Wan Amir Nizam (School of Health Sciences, Universiti Sains Malaysia, 2016)
Benincasa hispida, Bh (winter melon) is a good source of natural sugars, amino acids, organic acids, mineral elements and vitamins. This study was designed to explore the glycaemic effect of Bh aqueous extract in diabetic rats. Male Sprague-Dawley rats (250-350g) were induced to become diabetic with streptozotocin (STZ, 45mg/kg intraperitoneal). The Bh aqueous extracts of 100, 250 and 500 mg/kg and metformin were administered through oral gavage to determine their effects on fasting blood glucose (FBG) and oral glucose tolerance test. The dose of 250 mg/kg was found to be the most effective dose and it decreased blood glucose level (BGL) by 11.8% in normal healthy rats after 6H of administration. The same dose also caused a marked reduction in BGL of 33.1% in normal rats, 38.7% in severe diabetic rats and 64.7% in mildly diabetic rats in OGTT after 3H of oral administration of the extract. The changes of BGL were not significant compared to normal rats. It shows that the extract is diabetic-friendly since the blood glucose levels were stable throughout the study period. These trends of BGL reduction show that Bh aqueous extract is diabetic friendly.